The Influence of the Quality of E-Performance Consulting Services and the Satisfaction of Human Resource Managers of Regional Agencies on the Utilization of the E-Performance Application of the State Civil Service Agency (Study on the Work Area of Regional Office XI of the State Civil Service Agency) - Munayang, Tonny; Masengi, Evi Elvira; Tumbel, Goinpeace (Technium Social Sciences Journal, 2025)
The purpose of this study was to analyze the effect of the quality of e-Performance consultation services (X1) and the satisfaction of regional agency human resource managers (X2) on the utilization of the e-Performance application (Y). This study examines the utilization of the e-Performance application of the State Civil Service Agency (BKN) in an effort to modernize the performance governance of the State Civil Apparatus (ASN) in Indonesia, which is designed in accordance with the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 6 of 2022. This research uses a type of field research with a quantitative approach through inferential statistical processing of results. Data collection using questionnaires through area sampling techniques (cluster sampling) with 320 respondents. Hypothesis testing uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) with the SmartPLS version 4.0.9.9 application to test the relationship model between variables, including the effect of causality and intercorrelation. The results showed that the quality of e-Performance consultation services (X1) and satisfaction of regional agency human resource managers (X2) partially and simultaneously had a positive and significant effect on the utilization of the BKN e-Performance application (Y), with service quality having a substantial effect (path coefficient 0.611) and both variables being able to explain 62.2% of the variation in application utilization. The discussion of the research results consistently shows that the quality of e-Performance consultation services (X1) and the satisfaction of regional agency human resource managers (X2) have a positive and significant influence on the utilization of BKN's e-Performance application (Y). Service quality proves to be a dominant factor, where physical and interpersonal aspects greatly influence user perceptions. Meanwhile, manager satisfaction is driven by motivator factors such as achievement and recognition, which confirms the relevance of the two-factor theory in a bureaucratic context, although hygiene factors such as compensation still require attention. Simultaneously, these two variables, along with the dimensions of Technology Acceptance and Use Theory such as performance expectancy, effort expectancy, social influence, and facility conditions, are able to explain the shift in public administration towards a more humanistic and adaptive approach (New Public Service).